Anterolateral Ligament Repair Augmented With Suture Tape in Acute Anterior Cruciate Ligament Reconstruction - Edoardo Monaco, M.D.; Daniele Mazza, M.D.; Andrea Redler, M.D.; Piergiorgio Drogo, M.D.; Megan Rianne Wolf, M.D.; Andrea Ferretti, M.D. (Arthroscopy Techniques, 2019)
Several extra-articular surgical techniques in addition to anterior cruciate ligament reconstruction have been proposed to better restore rotational instability of the knee. One option is surgical repair of the anterolateral ligament in acute cases to achieve an anatomic reconstruction. An additional augmentation to the repair could allow a load-sharing—and thus protective—effect for the repair during the healing process. The purpose of this Technical Note is to describe a primary repair of the anterolateral ligament with suture tape augmentation (Internal Brace; Arthrex, Naples, FL) in a patient with an acute anterior cruciate ligament tear.